Development of a UPLC-ESI-MS/MS method for the determination of triamcinolone acetonide in human plasma and evaluation of its bioequivalence after a single intramuscular injection in healthy volunteers - Zhao, Pengfei; Qi, Ying (Frontiers in Pharmacology, 2023)
Introduction: Triamcinolone acetonide (TA) is commonly used in the treatment of various inflammatory conditions. To ensure its efficacy and safety, it is important to accurately determine its concentration in human plasma and evaluate its bioequivalence. In this study, an efficient ultra-performance liquid chromatography-electrospray ionization-tandem mass spectrometry (UPLC-ESI-MS/MS) method was developed for the quantification of TA in human plasma after a single intramuscular injection. The internal standard used in this method was cortisone acetate (CA). Methods: TA and CA were extracted from plasma using ethyl acetate and N-hexane (4:1, v/v), separated on a C18 reverse-phase column with a mobile phase of acetonitrile-water containing 1% formic acid (55:45, v/v), and analyzed by UPLC-ESI-MS/MS. Multiple-reaction monitoring was performed using the transitions m/z 435.4→397.3 for TA and m/z 403.4→163.1 for CA. Results: The developed UPLC-ESI-MS/MS method demonstrated linearity over a concentration range of 0.53–21.20 ng/mL, with a lower limit of quantification of 0.53 ng/mL. The intra- and inter-run precision values ranged from 3.007% to 9.960% and 3.528% to 11.26%, respectively. The intra- and inter-run accuracy ranges were −1.962% to −6.577% and −3.371% to 0.348%, respectively. The matrix effect, extraction recovery, and stability of TA all met the acceptance criteria recommended by the National Medical Products Administration (NMPA) for bioassays. In healthy volunteers who received a single intramuscular injection of 80 mg of either the test or reference formulation of TA, various pharmacokinetic parameters were determined. Cmax was found to be 8.616 ± 1.232 and 8.285 ± 1.218 ng/mL for the test and reference formulations, respectively. Tmax was approximately 1.833 ± 0.243 and 1.861 ± 0.230 h. The t1/2 was calculated to be 181.249 ± 78.585 and 201.782 ± 83.551 h. AUC0-720 was 835.642 ± 297.209 and 830.684 ± 331.168 ng h/mL, AUC0-∞ was 991.859 ± 355.939 and 1018.665 ± 420.769 ng h/mL for the test and reference formulations, respectively. The average relative bioavailability of TA, determined using AUC0-720, was 105.4 ± 26.9%. Bioequivalence was evaluated through variance analysis and a double unilateral test, and the 90% confidence intervals of AUC0-720, Cmax, and AUC0-∞ were 92.8%–113.4%, 99.1%–109.1%, and 89.7%–110.9%, respectively (all p > 0.05). Discussion: These results met the bioequivalence criteria set by the NMPA, indicating that the developed UPLC-ESI-MS/MS method accurately determined TA concentrations in the plasma of healthy Chinese volunteers and that the test and reference formulations exhibited bioequivalence in these individuals.